Direct Micropatterning of Initiator Layers for Surface-initiated ATRP: Spatially-regulated Growth of Polymer Brush and Subsequent Copper Electroless Plating. (24th July 2019) - Sato, Tomoya; Urata, Chihiro
Abstract: Direct patterning of initiator layers for surface-initiated atom transfer radical polymerization was successfully demonstrated on bare polyimide substrates based on an inkjet printing using a simple sol-gel solution of ( p -chloromethyl)phenyltrimethoxysilane and tetraethoxysilane. Using this approach, line-shaped initiator layers with a hundred of micrometer-scale width could be successfully patterned without specific pre-treatments of polyimide film surfaces. We also confirmed that they could serve as ideal templates for spatially-defined formation of nitrogen-containing polymer brushes and subsequent electroless Cu plating on non-conducting polyimide films with a reasonable growth rate and adhesion strength.